1985
DOI: 10.1172/jci111901
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of nephrogenic diabetes insipidus due to chronic administration of lithium in rats.

Abstract: A polyuric syndrome with nephrogenic diabetes insipidus (NDI) is a frequent consequence of prolonged administration of lithium (Li) salts. Studies in the past, mainly the acute and in vitro experiments, indicated that Li ions can inhibit hydroosmotic effect of 18-arginineivasopressin (AVP) at the step of cAMP generation in vitro. However, the pathogenesis of the NDI due to chronic oral administration of low therapeutic doses of Li salts is not yet clarified. We conducted a comprehensive study to clarify the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
12

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 33 publications
8
63
1
12
Order By: Relevance
“…Although the mechanisms by which hypokalemia causes nephrogenic diabetes insipidus are a matter of contention, it appears to be due to a reduction in the production of cAMP (the second messenger for vasopressin action) in response to vasopressin, either by direct inhibition of adenylate cyclase (2,16,25) or via increased prostaglandin production (14). Our previous observation that lithium causes a decrease in AQP2 expression could also be explained by this mechanism, as the lithium-induced polyuria is thought to be due to an inhibition of adenylate cyclase (26,27). This would suggest that the modulatory effect of vasopressin on AQP2 expression is mediated via the same (V 2 ) receptors that mediate the acute antidiuretic response.…”
Section: Discussionmentioning
confidence: 98%
“…Although the mechanisms by which hypokalemia causes nephrogenic diabetes insipidus are a matter of contention, it appears to be due to a reduction in the production of cAMP (the second messenger for vasopressin action) in response to vasopressin, either by direct inhibition of adenylate cyclase (2,16,25) or via increased prostaglandin production (14). Our previous observation that lithium causes a decrease in AQP2 expression could also be explained by this mechanism, as the lithium-induced polyuria is thought to be due to an inhibition of adenylate cyclase (26,27). This would suggest that the modulatory effect of vasopressin on AQP2 expression is mediated via the same (V 2 ) receptors that mediate the acute antidiuretic response.…”
Section: Discussionmentioning
confidence: 98%
“…NDI and reduced expression ofAQP2. It is well established that lithium often causes a vasopressin-resistant urinary concentrating defect, i.e., NDI (2,3), associated with structural changes in the medullary collecting ducts (22) and that the rat provides a useful animal model of this (5,23 Figure 6. Immunoblots comparing AQP2 expression in inner medulla of lithium-treated rats (L) with (a) lithium-treated rats either thirsted for 48 h (T) or (b) infused with dDAVP for 7 d (V).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that lithium acts by inhibiting adenylate cyclase activity in the collecting duct principal cells (2,5), thus preventing the production of cAMP, the second messenger for vasopressin. Prostaglandins may (6) or may not (7) play a part in this inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…While lithium usually causes impaired urine concentration, only about 15% of patients taking lithium for >15 years develop full-blown NDI [74,82]. Lithium's mechanism in causing NDI is unknown and a variety of mechanisms have been proposed -one of which is by decreasing cellular cAMP, causing decreased insertion of AQP2 into the apical membrane [83,84]. Other research shows that lithium's action is likely not due to cAMP, but rather, to AQP2 transcription reduction and AQP2 mRNA degradation [85].…”
Section: Nephrogenic Diabetes Insipidus (Ndi)mentioning
confidence: 99%